Sexual Stigma and Self-Actualization of Persons with Disabilities - Santoso, Yoga Budhi; Tukimin, Sunardi; Rochyadi, Endang; Aprilia, Imas Diana; Juhanaini, Juhanaini; Wibowo, Setyo Wahyu; Fatimatuzzahra, Ana; Ridwan, Prinanda Gustarina; Rahma, Zulfa; Novianti, Ranti (Department of Special Education, 2025)
This study aims to examine the stigma experienced by persons with disabilities, focusing on physical and sexual stigma and its relationship with self-actualization. Using a qualitative approach, the study involved 11 individuals with disabilities aged 20–31 years from various regions in Indonesia. Data were collected through questionnaires addressing sources and forms of stigma, as well as participants’ perceptions of their ability to achieve self-actualization, particularly in romantic and sexual relationships. Findings indicate that more than half of the respondents experienced stigma related to their physical condition, especially from family and neighborhood environments. Sexual stigma was less prevalent, with only a quarter of participants reporting such experiences, likely due to the cultural taboo surrounding sexuality in Indonesia. Notably, male participants were more likely to face stigma from family members, while females encountered it more in social settings. Despite facing stigma, the majority of respondents maintained a positive belief in their ability to form fulfilling relationships and achieve self-actualization. Only one respondent expressed doubt about finding a suitable partner. These findings suggest that while stigma remains a persistent issue, it does not uniformly hinder self-actualization, as individual resilience, religious beliefs, and social support play moderating roles. Further research with a larger and more diverse population is needed to better understand how stigma impacts individuals with disabilities across different cultural and social contexts.